2017
DOI: 10.1504/ijarge.2017.084038
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture land suitability evaluation for wheat cultivation using geomatics for Patan District, India

Abstract: Abstract:Crop land suitability for wheat crop is carried out in the Patan District of North Gujarat, India. There are many factors which affect the land suitability for wheat cultivation like land use, land cover,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, the analysis of this study showed that over three-fourths of the crop's highly suitable highland area lies in the range of gentle to flat slope areas. Studies also confirmed that topography determines the agricultural crops' yields [ 30 , 43 , 44 ]; Zhu et al, 2023). The Eragrostis tef Zucc crop cultivated in temperate and subtropical agro-ecological zones of flat-to-gentle slope areas produced high crop yields compared to high altitude (>2800 m.a.s.l) of steep to very steep slope areas in Dabo Hana district, south-west Ethiopia [ 33 ].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the analysis of this study showed that over three-fourths of the crop's highly suitable highland area lies in the range of gentle to flat slope areas. Studies also confirmed that topography determines the agricultural crops' yields [ 30 , 43 , 44 ]; Zhu et al, 2023). The Eragrostis tef Zucc crop cultivated in temperate and subtropical agro-ecological zones of flat-to-gentle slope areas produced high crop yields compared to high altitude (>2800 m.a.s.l) of steep to very steep slope areas in Dabo Hana district, south-west Ethiopia [ 33 ].…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, the farmers of each sub-district, together with the technical and technological support of the Agricultural and Rural Development office, should produce the recommended cereal crops on the right parcel at the right time. Accordingly, it has also been shown that land degradation in highland areas of the sub-tropical is highly accelerated on parcels of poor land management practices while it is prone to decrease in well-managed areas [ 16 , 44 , 46 , 53 ]. The same pattern has also been highlighted that inapt agricultural land use coupled with land resource destruction leads to inefficient utilization of crop yield, which results in food insecurity in the great Mwea region, Kenya [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AHP method is considered among the best available approaches of MCDA, which was used for assessing and analyzing land-use suitability for different crops [12,[34][35][36][37]. The pairwise comparison matrix was created on the basis of the relative importance of one criterion over another for determining the parameter weights, as per the AHP preference scale (Table 3).…”
Section: Weight Determination Using the Ahp Methods Of Mcdamentioning
confidence: 99%
“…It influences such important soil properties as soil water availability, infiltration rate, drainage, tillage conditions and capability to retain nutrients [23]. Soil depth is important because it provides insight into the growth of roots and the availability of moisture and air within the root zone [24]. Soil pH is a master variable in soils because it controls many chemical and biochemical processes operating within the soil.…”
Section: Criteria Selection Description and Sourcementioning
confidence: 99%